The Penguin dictionary for writers and editors - Bryson, Bill (Viking, 1991)
Jacuzzi or jacuzzi? brussels sprouts or Brussels sprouts? Hapsburg or Habsburg? liquefied or Liquified? whodunit or whodunnit? bogey, bogie or bogy? Moslem or Muslim? V-E Day or V.E. Day? Written English is full of pitfalls and confusions, even for native speakers and writers of the language. Covering spelling, capitalization, plurals, hyphens, abbreviations, foreign names and phrases and British and American usages, this book provides a guide through the controversies and disputes. It will be an indispensable companion to all who work with the written word - writers, journalists, secretaries, copy- editors, editors and publishers - aiming to give rulings that are both authoritative and commonsensical yet avoid the pedantries of so much writing about the English language. --Book Jacket